ANTECEDENTS OF ORGANIZATIONAL COMMITMENT AND ITS INFLUENCE ON THE PERFORMANCE OF BENER MERIAH POLRES PERSONNEL - Siswoyo Adi Wijaya; Herman Fithra; Naufal Bachri; Marbawi; Ibrahim Qamarius; Mariyudi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims at the influence of organizational culture and transformational leadership on personnel performance with organizational commitment as an intervening variable to the Bener Meriah police station. For the dependent variable of this study is organizational culture and transformational leadership, the independent variable is the personnel performance of the police station. Intervening variables are organizational commitment. The population in this study was the Police Personal of the Bener Meriah District Police which numbered 442, the sampling technique used proportionate stratified random sampling and obtained a sample of 170 respondents who were police officers of the Bener Meriah police station, the research method used was a quantitative method for data analysis method using Structural Equation Modeling (SEM)..